Impelementasi pendididkan sex pada anak usia dini di sekolah - Sarah Emmanuel Haryono; Henni Anggareni; Siti Muntomimah; Didik Iswahyudi (JAPI (Jurnal Akses Pengabdian Indonesia), 2018)
Sex education in Indonesia is still a controversy, there are still many community members who have not agreed on sex education at home or at school. In general, the public view of sex education is considered "taboo" to talk about children, especially children of early age. the community often holds that it is not yet time for children of early age to understand about things related to sexuality. People assume that there is a time they will understand it naturally. that sex education from an early age is an effort to provide understanding to children from an early age adapted to their developmental stages (cognitive, attitude, and behavioral aspects) about the functioning of sexual devices and instinctive problems that arise, guidance on the importance of maintaining and maintaining their sex organs, and understanding of healthy intercourse and the risks that can occur around sexual problems. It takes concrete understanding in kindergarten teachers about how to implement sex education in early childhood at school. Understanding the importance of sex education in early childhood is provided in the workshop area, where teachers will have understanding and skills in implementing sex education in early childhood in accordance with the development within the child. Teachers are able to create a daily learning plan that contains sex education in it. It is hoped that the implementation of sex education in early childhood at school can help prevent children from sexual violence.